Inactivation of Salmonella enterica and shiga toxin-producing Escherichia coli on desiccated shredded coconut by high voltage atmospheric cold plasma - Durand, Tonia S.; Mendonca, Aubrey; Fortes-Da-Silva, Paulo; Brehm-Stecher, Byron; Boylston, Terri; Thomas-Popo, Emalie; Wan, Zifan; White, Shecoya (Frontiers in Food Science and Technology, 2023)
The main objective of the present study was to determine the efficacy of dielectric barrier discharge (DBD) high voltage atmospheric cold plasma (HVACP) at 70 kV for inactivating Salmonella enterica and shiga-toxin-producing Escherichia coli (STEC) on desiccated shredded coconut. Additional objectives were to evaluate sub-lethal injury in pathogen survivors, and selected quality characteristics of the coconut as affected by HVACP. Shredded coconut inoculated with ∼7.74 log10 CFU/g S. enterica or STEC, was exposed to HVACP (70 kV) for 3–15 min (S. enterica) and up to 5 min (E. coli). Non-HVACP-treated, inoculated coconut served as control. Samples were held at 23 ± 1°C for 24 h after HVACP treatment, and analyzed for survivors via the plate count method using thin agar layer (TAL) media and selective (SEL) agar. For each pathogen, differences in numbers of survivors on TAL medium and selective agar were used to evaluate sub-lethal injury. Color and texture of the coconut were determined using a ColorFlex EZ Spectrophotometer and a TA. XT Plus C Texture Analyzer, respectively. HVACP treatments significantly decreased the initial numbers of viable S. enterica and STEC (p < 0.05) with more survivors consistently recovered on TAL media compared to selective agar. Reductions (log10 CFU/g) of STEC and S. enterica after 3 min of HVACP treatment were 1.97 and 1.56, respectively (p < 0.05) based on survivors on TAL medium. A greater extent of sub-lethal injury was observed in STEC survivors compared to S. enterica (p < 0.05). The TAL method allowed detection of sub-lethally injured pathogens in HVACP-treated coconut that would have otherwise remained undetected if only selective agar media were used. There were minimal changes in color and texture of the coconut after HVACP (70 kV) treatment for 12 min. Based on these results, HVACP (70 kV) has good potential for inactivating enteric pathogens in desiccated shredded coconut to improve the microbial safety of this popular food ingredient with minimal effect on product color and texture.